Histórico do uso da terra e composição de gerromorpha (insecta: subordem heteroptera) em igarapés da Transxingu - COSTA, Iluany da Silva (Universidade Federal do Pará, 2025)
The Amazon Forest faces threats due to the increasing exploitation of natural resources driven by the economic growth of the region, intensified since the exploitation of rubber between 1879 and 1912. Since the 1960s, the government has implemented economic development programs, territorial occupation and construction of highways, such as BR230, also known as Transamazônica. This highway had a significant impact on the southwest region of Pará, especially in the Xingu River basins, contributing to disorderly deforestation and harming biodiversity, especially on the banks of water bodies. To deal with environmental problems, several analysis and monitoring methods have been developed, including remote sensing, which allows large areas to be studied in a short time. Biological monitoring is also used, as some organisms, such as aquatic insects from the infraorder Gerromorpha, are sensitive to environmental changes and can indicate the quality of the habitat. Therefore, a recent study analyzed the history of land use in the region over the last 30 years and evaluated the composition of the Gerromorpha infraorder in Transxingu streams. A large loss of vegetation cover has been observed in recent decades, especially close to roads, often related to livestock farming. However, there has been a reduction in deforestation over time, possibly due to conservation measures, such as the Action Plan for the Prevention and Control of Deforestation in the Legal Amazon (PPCDAm), creation of extractive reserves, recognition of indigenous lands and the Cadastre Rural Environmental (CAR). In the study of the composition of the Gerromorpha infraorder in the Transxingu streams, it was found that many samples were influenced by deforestation over the years. Furthermore, it was found that the integrity index of the stream's physical habitat can be more effective than geospatial metrics in assessing environmental impact. Although there were no significant differences in the Gerromorpha community between preserved and altered environments, a variation in the abundance of these organisms was noticed along environmental gradients. This indicates that the community responds to changes in the environment, regardless of the presence of specific bioindicator species. Therefore, there is a need for more studies in highly preserved environments to better understand these dynamics.